Global, regional, and national larynx cancer burden and health inequality analysis from 1990 to 2021 with a prediction from 2022 to 2040 - Junjie Jiang; Zhongfang Xia; Wei Yao (Frontiers in Oncology, 2025)
BackgroundTo assess the global burden and health inequalities of laryngeal cancer from 1990 to 2021 and to project future trends up to 2040.MethodsUsing the 2021 Global Burden of Disease (GBD) data, this study analyzed trends in prevalence (ASPR), incidence (ASIR), mortality (ASDR), and disability-adjusted life years (DALYs) of laryngeal cancer from 2009 to 2021, with annual percentage change (EAPC) estimates. Inequalities were assessed using the Slope Index of Inequality (SII) and Concentration Index (CI), while future projections to 2040 were made using the Bayesian Age-Period-Cohort (BAPC) model.ResultsIn 2021, there were approximately 1.1 million global laryngeal cancer cases (an age-standardized prevalence rate (ASPR) of 12.56 per 100,000, 95% UI: 11.76–13.49). The age-standardized incidence rate (ASIR), the age-standardized mortality rate (ASDR), and disability-adjusted life years (DALYs) rates were 2.29, 1.35, and 35.8 per 100,000, respectively. Significant disparities were observed across regions and SDI levels: high SDI regions had the highest incidence rates, while middle-low SDI regions experienced the greatest mortality and DALY burden. Central Europe had the highest ASPR, ASIR, and DALY rates, while the Caribbean reported the highest ASDR. From 1990 to 2021, the DALYs Slope Index of Inequality (SII) dropped from 37.75 (95% CI: 26.92–48.58) to -11.57 (95% CI: -22.14 to -1.00), indicating improved equity in health outcomes between high- and low-income countries.ConclusionsWhile the global burden of laryngeal cancer is projected to decline by 2040, significant health disparities persist. Addressing these inequalities will require sustained efforts, including equitable resource allocation, improved access to healthcare, and targeted public health interventions.